Environmental pollution and the need for environmental awareness - Noman Ibrahim, Nawfal; Ahmed Abdul Rahman, Mayada (Al-Adab Journal, 2020)
The environment and its problems are of great importance, so environmental issues have imposed themselves on various levels and levels, whether they are local, regional or international. Which encouraged countries to hold conferences and seminars to put in place laws that limit that risk that threatens all living organisms, including the person who is the primary responsible for these problems, and environmental pollution is a problem of the modern era and one of its most prominent issues that threatens all countries. The Iraqi reality is not in isolation from this pollution, and what made matters worse the wars that Iraq witnessed, the economic blockade and the collapse of the entire infrastructure, which had negative effects on the Iraqi environment. In this chapter, the first two topics are entitled (environmental awareness), while the second topic (development and environmental awareness).